Understanding Anak Dalam Tribe students’ experiences with deep learning-based AI-generated voice cloning of Tumenggung - Wardani, Diah Octavia Kusuma; Fitrah, Yundi; Hadiyanto; Rahmawati, Sophia; Muhsinin, Umil (Proceedings of International Conference on Research in Education, 2025)
Education for Suku Anak Dalam has always represented an encounter between two worlds of knowledge about the modern logic of schooling and the oral wisdom sustained by the spiritual authority of the Tumenggung. This study explores that question by integrating AI-generated voice cloning of the Tumenggung’s voice into a deep learning-based approach. Drawing on a qualitative approach framed by third-generation Cultural-Historical Activity Theory, we examine how this digital artifact mediates the relationships among teachers, students, and indigenous values. The findings reveal that the Tumenggung’s digital voice is not merely a replica, but a cultural dialogue space that rekindles a sense of belonging, fosters affective engagement, and builds epistemic bridges between culture and technology. Ultimately, the study suggests that the essence of educational innovation does not lie in machines that imitate humans, but in humans who rediscover their humanity through technology.
Keywords: AI-EdTech; AI-generated voice cloning; Anak Dalam Tribe; cultural-historical activity theory; deep learning